Outcomes of V-Y Quadricepsplasty for the Management of Genu Recurvatum Deformity in Congenital Dislocation Knee - Pabitra Kumar Sahoo; Sourav Deb; Deepak Kumar Singh; Pramod Kumar Parida (Indian Journal of Physical Medicine & Rehabilitation)
Background: Congenital dislocation knee (CDK) is a rare congenital anomaly clinically presented with genu recurvatum deformity. In early reported cases, conservative management with manipulation and serial casting once a week for up to 4 weeks can be successful. Surgical methods of deformity correction include percutaneous quadriceps recession, Z-plasty, V-Y quadricepsplasty (VYQ), and Achilles tendon reconstruction for the reconstruction of the quadriceps tendon. Very few studies are reported in Indian literature describing the outcomes of surgical intervention in such an uncommon congenital deformity. The purpose of this study is to evaluate the outcomes of VYQ in CDK. Materials and Methods: Ten children with CDK with a mean age of 44.4 months, who met the inclusion criteria, were included in the study. All the children had undergone VYQ as described by Curtis and Fisher and subsequently modified by Tercier and Shah. Outcome measures such as active and passive knee range of motion, quadriceps power, and modified knee functional scoring system were assessed at the final follow-up. Results: Most of the children in the current study achieved knee flexion of >90° with an average flexion of 90.5° + 21.73 (standard deviation), and 50% of them achieved quadriceps power Grade 4 or more (median 3.5). Modified knee function score was good in 60% of cases, fair in 20%, and excellent function in 10% of cases. Conclusion: Adequate knee flexion without quadriceps weakness and good knee function can be achieved by VYQ in CDK. This is a simple surgical procedure that can be easily learned with a flat learning curve.